A Stakeholder Analysis of the Disaster Risk Reduction Policy Subsystem in Mozambique. Issue 1 (March 2014) - Koivisto, Jenni E.
<x xml:space="preserve">Abstract</x> Climate change is expected to increase the frequency and magnitude of climate related hazards in many countries. Due to this, disaster risk reduction (DRR) policy has gained a lot of attention in recent years. DRR policies address complex problems that require inputs from a variety of stakeholders and hence a multi‐stakeholder approach has been advocated widely. However, the practice of DRR policymaking is challenging and therefore new tools are needed to better understand the political context of DRR policymaking. This article utilizes an Advocacy Coalition Framework (ACF) approach to describe the political context of the DRR policy subsystem in Mozambique. Through a stakeholder analysis, the article seeks to empirically define subsystem boundaries and to identify belief systems and key actors therein. The results indicate that the actors can be divided into two advocacy coalitions, formed around extant approaches to DRR: disaster management and development. The article concludes with reflections on the applicability of an ACF approach to stakeholder analysis and as a tool for understanding policy disputes and coordination challenges in complex settings, such as DRR governance.